The Influence of School Culture and Principal Managerial Competence on Elementary School Teacher Performance in a Remote Indonesian District: A Quantitative Study - Budi Prayogo; Andi Rahman; Pahlawan Pahlawan (Yayasan Sembilan Pemuda Indonesia, 2026)
This quantitative study examines the influence of school culture and principal managerial competence on elementary school teacher performance in Karang Agung Ilir District, Banyuasin Regency, Indonesia—a remote area with significant geographic and infrastructural constraints. Using an explanatory correlational design, data were collected from 79 public elementary school teachers selected through proportional random sampling. Validated and reliable Likert-scale questionnaires were employed. Data were analyzed using simple and multiple linear regression. Findings reveal that school culture has a positive and significant effect on teacher performance (β = 0.967, t = 21.512, p < 0.001), contributing 85.7% (R² = 0.857). Principal managerial competence also demonstrates a positive and significant effect (β = 0.955, t = 21.239, p < 0.001), contributing 85.4% (R² = 0.854). Simultaneously, both variables significantly predict teacher performance (F = 294.892, p < 0.001), with a combined contribution of 88.6% (R² = 0.886). These results indicate that in resource-limited, geographically isolated schools, a conducive school culture and effective principal managerial competence are critical determinants of teacher performance. The study contributes empirical evidence from an understudied remote elementary school context, extending organizational culture and educational leadership theories. Practically, it recommends targeted professional development for principals in managerial functions and intentional cultivation of collaborative school culture to enhance teacher performance in similar marginalized settings.